Meneropong Teks dalam Konteks: Katekismus Heidelberg P/J 53 - Freddy Gunawan (Sekolah Tinggi Teologi SAAT (Southeast Asia Bible Seminary), 2017)
The Heidelberg Catechism reflects a rich heritage within the Church that adheres to the Reformed tradition. It contains a rich strain of doctrine pertaining to the doctrine of the Holy Spirit. Explicitly, within the Heidelberg Catechism, the teaching regarding the doctrine of the Holy Spirit as a Member of the Godhead is found only in Question/Answer 53. Of course, this does not mean that the only teaching on the subject of the doctrine of the Holy Spirit within the Heidelberg Catechism is recorded in this section alone. The purpose of this essay is an attempt to conduct an analysis of the doctrine of the Holy Spirit, specifically Q/A 53, from three different contexts: the historical setting which reflects the historical context in which the Heidelberg Catechism was formulated, a macro and micro textual analysis of Q/A 53 within the context of the Heidelberg Catechism, and finally, the relevancy of the document for the contemporary context, especially focusing upon the Indonesian context.